2020
DOI: 10.2147/ccid.s238358
|View full text |Cite
|
Sign up to set email alerts
|

<p>An Open-Label Single-Arm, Monocentric Study Assessing the Efficacy and Safety of Natural Pterostilbene (<em>Pterocarpus marsupium</em>) for Skin Brightening and Antiaging Effects</p>

Abstract: Background: Both intrinsic and environmental factors play a role in premature ageing of the skin. Natural extracts have been extensively used to reduce the signs of ageing in recent years. Pterostilbene is a natural analog of resveratrol with therapeutic properties against numerous diseases mainly due to its ability to reduce reactive oxygen species. Methods: We studied the anti-aging and skin brightening effect of a 0.4% formulation of natural pterostilbene in healthy volunteers (N=38) in an open-label, singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…PTS is known to have antioxidant, anti-inflammatory and anti-aging activities [26]. Recent clinical trials have shown through dermatological assessment, instrumental analysis and image analysis that PTS can reduce skin aging and brighten skin tone [27]. However, it is not known whether PTS can prevent PM-induced keratinocyte damage.…”
Section: Discussionmentioning
confidence: 99%
“…PTS is known to have antioxidant, anti-inflammatory and anti-aging activities [26]. Recent clinical trials have shown through dermatological assessment, instrumental analysis and image analysis that PTS can reduce skin aging and brighten skin tone [27]. However, it is not known whether PTS can prevent PM-induced keratinocyte damage.…”
Section: Discussionmentioning
confidence: 99%
“…The skin moisturization and elasticity were improved with no adverse effects [109] Resveratrol in SLNs, NLCs, and nanoemulsions…”
Section: Humanmentioning
confidence: 98%
“…Oral administration of grape peel extract and resveratrol exerted the anti-photoaging effects on UVB-induced skin wrinkle formation via promotion of Nrf2/HO-1 signaling cascades ( Kim et al, 2019 ). In addition, a formulation containing 0.4% pterostilbene, the resveratrol analog, extracted from the dried heartwood of Pterocarpus marsupium Roxb., showed substantial reduction of aging markers and improvement of wrinkles, skin hydration elasticity in healthy volunteers ( Majeed et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%